Turbine thermomechanical modelling during excessive axial movement and overspeed - Eryilmaz, Ibrahim; Pachidis, Vassilios (Cambridge University Press, 2019)
This manuscript discusses the numerical (finite element) and analytical modelling of structural interactions between gas turbine components in case of excessive axial movement and overspeed. Excessive axial movement, which may occur after a shaft failure, results in contact between rotating and static turbine components under high forces. These forces create friction which can act as a counter torque, potentially retarding the ‘free-rotating’ components. The study is based on a shaft failure scenario of a ‘three-shaft’, high ‘by-pass’ ratio, civil ‘large-fan’ engine. Coupled analytical performance and friction methods are used as standalone tools to investigate the effect of rubbing between rotating and stationary components. The method is supported by ‘high-fidelity’, ‘three-dimensional’, thermomechanical finite element simulations using LS-DYNA software. The novelty of the work reported herein lies in the development of a generalized modelling approach that can produce useful engine design guidelines to minimize the terminal speed of a free running turbine after an unlocated shaft failure. The study demonstrates the advantage of using a fast analytical formulation in a design space exploration, after verifying the analytical model against finite element simulation results. The radius and the area of a stationary seal platform in the turbine assembly are changed systematically and the design space is explored in terms of turbine acceleration, turbine dislocation rate and stationary component mass. The radius of the friction interface increases due to the increasing radius of the nozzle guide vane flow path and stationary seal platform. This increases the frictional torque generated at the interface. It was found that if the axial dislocation rate of the free running turbine wheel is high, the resulting friction torque becomes more effective as an overspeed prevention mechanism. Reduced contact area results in a higher axial dislocation rate and this condition leads to a design compromise between available friction capacity, during shaft failure contact, and seal platform structural integrity.
Keywords: Thermal structural FEA; LS-DYNA; shaft failure; turbine overspeed